2011
DOI: 10.1002/art.33329
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in enhancement of the expression and function of aggrecanases by hyaluronan oligosaccharides

Abstract: Objective Small hyaluronan (HA) oligosaccharides serve as competitive receptor antagonists to displace HA from the cell surface and induce cell signaling events. In articular chondrocytes this cell signaling is mediated by the HA receptor CD44 and induces stimulation of genes involved in matrix degradation such as matrix metalloproteinases as well as matrix repair genes including collagen type II, aggrecan and HA synthase-2. The objective of this study was to determine changes in the expression and function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Cell Culture-Primary bovine articular chondrocytes were isolated from the metacarpophalangeal joints of 18 -24-month-old adult steers as described previously (28,46). Primary human articular chondrocytes were isolated from knee cartilage obtained following joint replacement surgery, within 24 h after surgery and with institutional approval.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cell Culture-Primary bovine articular chondrocytes were isolated from the metacarpophalangeal joints of 18 -24-month-old adult steers as described previously (28,46). Primary human articular chondrocytes were isolated from knee cartilage obtained following joint replacement surgery, within 24 h after surgery and with institutional approval.…”
Section: Methodsmentioning
confidence: 99%
“…The fold increase in copy numbers of mRNA was calculated as a relative ratio of target gene to GAPDH (⌬⌬Ct), following the mathematical model introduced by Pfaffl (62) as described previously (28,46). Statistical Analysis-All data were obtained from at least three independent experiments performed in duplicate or triplicate.…”
Section: -Mu Inhibition Of Mmp Production Independent Of Ha Blockmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Tajima et al (35) indicated that OPN was involved in multidrug resistance by enhancing the binding of CD44 to HA. Ariyoshi et al (36) demonstrated disruptive changes in chondrocyte-matrix interactions by HA oligosaccharides, which induced matrix degradation and elevated levels of aggrecanase (ADAMTS4 and ADAMTS5) activity via the NF-κB signaling pathway. Yatabe et al (4) observed that HA2700 (2,700 kDa HA) suppressed aggrecan degradation in OA chondrocytes via the downregulation of IL-1α-induced ADAMTS4 expression through the CD44 and intracellular adhesion molecule 1 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%